Boronic acids as probes for investigation of allosteric modulation of the chemokine receptor CXCR3. - Bernat, Viachaslau; Admas, Tizita; Brox, Regine; Heinemann, Frank Wilhelm; Tschammer, Nuska (ACS Chemical Biology, 2014)
The chemokine receptor CXCR3 is a G protein-coupled receptor, which conveys extracellular signals into cells by changing its conformation upon agonist binding. To facilitate the mechanistic understanding of allosteric modulation of CXCR3, we combined computational modeling with the synthesis of novel chemical tools containing boronic acid moiety, site-directed mutagenesis, and detailed functional characterization. The design of boronic acid derivatives was based on the predictions from homology modeling and docking. The choice of the boronic acid moiety was dictated by its unique ability to interact with proteins in a reversible covalent way, thereby influencing conformational dynamics of target biomolecules. During the synthesis of the library we have developed a novel approach for the purification of drug-like boronic acids. To validate the predicted binding mode and to identify amino acid residues responsible for the transduction of signal through CXCR3, we conducted a site-directed mutagenesis study. With the use of allosteric radioligand RAMX3 we were able to establish the existence of a second allosteric binding pocket in CXCR3, which enables different binding modes of structurally closely related allosteric modulators of CXCR3. We have also identified residues Trp109(2.60) and Lys300(7.35) inside the transmembrane bundle of the receptor as crucial for the regulation of the G protein activation. Furthermore, we report the boronic acid 14 as the first biased negative allosteric modulator of the receptor. Overall, our data demonstrate that boronic acid derivatives represent an outstanding tool for determination of key receptor-ligand interactions and induction of ligand-biased signaling.

Development of Photoactivatable Allosteric Modulators for the Chemokine Receptor CXCR3 - Admas, Tizita; Bernat, Viachaslau; Heinrich, Markus; Tschammer, Nuska (ChemMedChem, 2016)
The CXCR3 receptor, a class A G protein-coupled receptor (GPCR), is involved in the regulation and trafficking of various immune cells. CXCR3 antagonists have been proposed to be beneficial for the treatment of a wide range of disorders including but not limited to inflammatory and autoimmune diseases. The structure-based design of CXCR3 ligands remains, however, hampered by a lack of structural information describing in detail the interactions between an allosteric ligand and the receptor. We designed and synthesized photoactivatable probes for the structural and functional characterization, using photoaffinity labeling followed by mass spectrometry, of the CXCR3 allosteric binding pocket of AMG 487 and RAMX3, two potent and selective CXCR3 negative allosteric modulators. Photoaffinity labeling is a common approach to elucidate binding modes of small-molecule ligands of GPCRs through the aid of photoactivatable probes that convert to extremely reactive intermediates upon photolysis. The photolabile probe N-[(1-[3-(4-ethoxyphenyl)-4-oxo-3,4-dihydropyrido[2,3-d]pyrimidin-2-yl]ethyl-2-[4-fluoro-3-(trifluoromethyl)phenyl]-N-1-[4-(3-(trifluoromethyl)-3H-diazirin-3-yl]benzylpiperidin-4-yl)methyl]acetamide (10) showed significant labeling of the CXCR3 receptor (80 %) in a [H]RAMX3 radioligand displacement assay. Compound 10 will serve as an important tool compound for the detailed investigation of the binding pocket of CXCR3 by mass spectrometry. A series of photoactivatable ligands was designed for labelling the allosteric pocket of the CXCR3 receptor, a class A G protein-coupled receptor involved in the regulation and trafficking of immune cells and thus a potential target for the treatment of inflammatory and autoimmune diseases. Compound 10 (pictured) bearing a 3-trifluoromethyl-3-phenyldiazirine group was identified as a promising tool for the study of the CXCR3 allosteric binding pocket.
Keywords: chemokine receptors; CXCR3; irreversible binding; photoactivatable ligands; photoaffinity labelling